MANAJEMEN KURIKULUM MUADALAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Ulfa Qomariatul Jannah Ulfa (CV Narasi Khatulistiwa Indonesia, 2026)
This study aims to analyze the planning, implementation, and evaluation of curriculum management in improving the quality of education at the Satuan Pendidikan Muadalah (SPM) of Al-Mashduqiah Islamic Boarding School. Curriculum management is an essential aspect of improving the quality of Islamic boarding school education because it functions as a guideline for organizing learning processes in a systematic, directed, and sustainable manner. This study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the head of the institution, boarding school caregivers, curriculum coordinators, teachers, and students as research informants. Data analysis was conducted through the stages of data reduction, data display, and data verification using content analysis, discourse analysis, and interpretative analysis. The findings revealed that curriculum planning was carried out through the development of educational and teaching aspects, cadre formation, infrastructure, financial resources, and boarding school welfare. Curriculum implementation was conducted through regular, intensive, and acceleration programs integrating religious education, general education, and character building. Curriculum evaluation was implemented periodically through supervision, routine meetings, and learning documentation. This study implies that the implementation of Muadalah-based curriculum management can effectively, adaptively, and sustainably improve the quality of Islamic boarding school education.